Transglutaminase-induced Cornea Collagen Crosslinking Effect on Central Corneal Thickness and Keratocyte Cell Density: Oral Presentation - Experimental Study - Ophthalmologist - PUSPITA HAPSARI SITORASMI; Yuniar Sarah Ningtiyas; Indri Wahyuni; Yulia Primatasari (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : This research is aimed to evaluate the effect of transglutaminase-induced corneal collagen crosslinking (CXL) on central corneal thickness (CCT) and keratocyte cell density in vivo. Methods : Twenty-eight white New Zealand rabbits were divided into four groups: the transglutaminase- induced CXL group, the epithelial-off CXL group, the transepithelial CXL group, and the control group. The ocular surface was treated with a 1 U/mL microbial transglutaminase solution, and both the epithelial-off and transepithelial groups were exposed to clinical ultraviolet A-riboflavin (UVA/RF). The efficacy of each group was evaluated on the 14th day after the procedures. Central corneal thickness was evaluated with Corneal Visualization Scheimpflug Technology (Corvis ST) and keratocyte cell density wad evaluated with histopathology examination. Results : Transglutaminase-induced CXL group exhibited the highest mean biomechanical CCT (370.14 ± 38.85) in comparison to the UVA/RF epithelial-off group (368.00 ± 25.48), the UVA/RF transepithelial group (369.86 ± 23.43), and the control group (365.14 ± 28.74). Still, there was no significant differences in both biomechanical CCT (p=0.990). Transglutaminase-induced CXL group had the highest mean of keratocyte cell density (43.26 ± 10.65) compared to UVA/RF epithelial-off (29.99 ± 4.79), UVA/RF transepithelial group (42.03 ± 6.55), and control group (34.36 ± 6.76). There was a significant difference between the group, with a p-value of 0.008. Conclusion : Transglutaminase shown that it produces favorable results for CCT and keratocyte density after CXL, which are two factors contributing to corneal rigidity. The outcomes are equivalent to riboflavin used as a conventional element in CXL.